2012
DOI: 10.1212/wnl.0b013e318248e568
|View full text |Cite
|
Sign up to set email alerts
|

CSF VILIP-1 predicts rates of cognitive decline in early Alzheimer disease

Abstract: Objective: Measures of neuronal damage/dysfunction are likely good surrogates for disease progression in Alzheimer disease (AD). CSF markers of neuronal injury may offer utility in predicting disease progression and guiding prognostic and outcome assessments in therapeutic trials. Visinin-like protein-1 (VILIP-1) has demonstrated potential utility as a marker of neuronal injury. We here investigate the utility of VILIP-1 and VILIP-1/A␤42 in predicting rates of cognitive decline in early AD.Methods: Individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
107
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 37 publications
6
107
4
1
Order By: Relevance
“…AD risk groups within the MCI groups of patients were defined by the levels of five CSF AD biomarkers (Aβ 1-42 , t-tau, p-tau 181 ,p-tau 199 , and ptau 231 ). We tested VILIP-1 effectiveness in early detection of AD in MCI patients, and confirmed previous observations that VILIP-1 is a useful biomarker in early AD diagnosis [12,17,[27][28][29][30]]. Additionally, we tested VILIP-1 potential in differentiating AD from other primary causes of dementia, and its ability in predicting disease progression.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…AD risk groups within the MCI groups of patients were defined by the levels of five CSF AD biomarkers (Aβ 1-42 , t-tau, p-tau 181 ,p-tau 199 , and ptau 231 ). We tested VILIP-1 effectiveness in early detection of AD in MCI patients, and confirmed previous observations that VILIP-1 is a useful biomarker in early AD diagnosis [12,17,[27][28][29][30]]. Additionally, we tested VILIP-1 potential in differentiating AD from other primary causes of dementia, and its ability in predicting disease progression.…”
Section: Discussionsupporting
confidence: 73%
“…Also, recent genome-wide association studies (GWAS) showed an association of polymorphisms in VILIP-1 and VILIP-3 genes with the occurrence of AD [25,26]. Altogether, these factors may contribute to neuronal cell death and to the increase of VILIP-1 in CSF of AD patients [12,17,[27][28][29][30]. VILIP-1 levels were also increased in plasma of AD patients [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pittsburgh compound B, or PIB) and positron emission tomography, or indirectly, by measuring low CSF beta-amyloid42 (Ab42) concentrations that correlate with amyloid deposition [3,[10][11][12][13][14]. Imaging and fluid biomarker studies have also shown potential to predict cognitive decline by measuring amyloid deposition [5], regional volumetric and metabolic changes in the brain [15][16][17], or specific changes in the CSF proteome (including concentrations of tau, YKL-40, VILIP-1, and calbindin, each in association with Ab42) [2,3,18,19]. CSF analysis may even allow classification of disease stage [20] and monitoring of acute changes in response to disease modifying therapies, as illustrated recently with gamma-secretase inhibitors [21].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of YKL-40 to Aβ42 predicts cognitive impairment as well as the best CSF biomarkers (Aβ42, t-tau, and p-tau) [83] , suggesting potential as a biomarker for preclinical AD. dementias, and that CSF VILIP-1/Aβ42 predicts cognitive impairment as well as tau/Aβ42 and p-tau181/Aβ42 [84,85] . …”
mentioning
confidence: 97%